The Ergonomics of the Islamic Ablution: Exploring Considerations for the Elderly in the Mosque - Sarah Aliya Che Hasbi; Sufian Hamat (Universitas Indraprasta PGRI, 2020)
A general observation on the state and condition of the ablution area at some mosques in the country has pictured the place as slippery and unsafe and not properly used and maintained. This has led to the assumptions that the design of the place had not thoroughly considered the ergonomic factors and right anthropometric of the users which has created discomfort in positioning oneself and accessing the fixtures during the act. The impact of the problems has never been rationalized and always overlooked particularly on how it may affect the elderly group that is has become very common and being repeated in the provision of the ablution area in other mosque’s design and development. In consideration of the pressing issues and needs for an appropriate ablution area as part of safety and cleanliness measures at Mosque or Surau, the design of the facility must be emphasized and be based on the needs and physical abilities of the users. This particular study on the ablution area is necessary as it has uncovered salient and common problem of the current design of the place. The methodology selected for the study was a combination of several methods. It encompassed onsite observation on the practical use and performance of the ablution area, interview survey on users’ practical experience and design assessment focusing on the ergonomic and anthropometric considerations of the place through measured drawing method. The results were triangulated to determine the overall performance of the present design of ablution area in facilitating spiritual obligation of the people. For the purpose, three different mosques in Kuala Nerus district namely Masjid UNiSZA (Universiti Sultan Zainal Abidin), Masjid UMT (Universiti Malaysia Terengganu) and Masjid Tok Jembal were selected as case studies. The study on the 3 sites of ablution area has displayed results indicating problems generally based on the location and proximity of water faucet and seating provision at the area which apparently were not based on the right ergonomic. This has created discomfort to the users and leaving messy and slippery ground after use.